Prognostic value of preoperative and postoperative serum CEA in colorectal signet ring cell carcinoma - Zheng, Yanan; Luo, Yang; Ji, Zuhong; Pan, Ying; Wang, Xiaohong; Liu, Fang; Liu, Lei; Shen, Shanshan; You, Qiang; Ling, Tao (Frontiers in Surgery, 2025)
BackgroundColorectal signet ring cell carcinoma (SRCC) is a rare and poorly prognosed tumor with limited established prognostic indicators. This study aims to investigate the prognostic value of serum carcinoembryonic antigen (CEA) in patients with colorectal SRCC.MethodsA retrospective, multicenter study was conducted to assess the association between CEA levels and survival outcomes in 942 patients with colorectal SRCC.ResultsPatients exhibiting preoperative CEA (preCEA)-positivity demonstrated significantly lower cancer-specific survival (CSS) compared to those with preCEA-negativity in both Chinese and SEER datasets (5-year CSS: 27.50% vs. 48.27%, P = 0.01; 34.37% vs. 48.47%, P < 0.05). This disparity in outcomes was particularly notable in advanced stages (III, IV and N2; all P values < 0.05), while no statistical significance was observed in earlier stages (I/II, N0 and N1; all P values > 0.05). Patients with preCEA and postoperative CEA (postCEA)-negativity showed similar CSS to those with preCEA-positivity and postCEA-negativity, but those with postCEA-positivity had worse prognosis. After accounting for potential confounders, preCEA and postCEA maintained as independent predictors for CSS (P < 0.05). The nomogram model incorporating preCEA (preCEA-model) showed a C-index value of 0.75, whereas the model incorporating postCEA (postCEA-model) exhibited a C-index value of 0.73.ConclusionsBoth preoperative and postoperative elevation of CEA levels were associated with adverse outcomes, with preoperative CEA demonstrating particularly significant predictive value in advanced-stage tumors. These findings propose that CEA could be a valuable tool for dynamically monitoring the prognosis of colorectal SRCC patients.